Use of Benime Application in Arabic Language Learning - Edar Hael; Luqman Hafiz; Changjiang Deng (Yayasan Adra Karima Hubbi, 2023)
Language is a very basic thing for every human being, not only for communication but also as a forum for the prosecution of knowledge. At this time, other languages are urgently needed because of the increasing circulation of information using other languages, as well as Arabic itself. In the process of learning Arabic, there are several problems or difficulties faced at the IT Ar-Rahman Palangki Elementary School. With the development of technology at this time, therefore technology can be a solution to the difficulties brought into the teaching and learning process of Arabic at SD IT Ar-Rahman Palangki. This is due to the technology that we can use to assist in making interesting learning media, especially applications that can be accessed on Android in the form of images, sounds, and moving animations, such as the Benime application. The benime app itself is an animated video maker app for a more interesting percentage.